SISTEM INFORMASI REKRUTMEN KARYAWAN BERBASIS WEBSITE - Sambodo Putro, Mohamad Doris; Susilowati, Meme (Fakultas Sains dan Teknologi, 2024)
Advances in technology, this recruitment information system aims to develop an employee recruitment information system specifically for the marketing division in a company. Currently, many companies still rely on conventional methods in the recruitment process, so it is necessary to increase efficiency through the use of information systems. This research uses the Waterfall method approach in system development, with a focus on user needs analysis, system design, and implementation. The system developed allows admins, managers and prospective employees to access information related to the selection process more efficiently. Test results show significant improvements in time efficiency and employee selection accuracy. The conclusion of this research confirms that the implementation of a website-based recruitment information system provides an effective solution to speed up and simplify the recruitment process, support accurate decision making, and increase the efficiency of human resource management in companies.